2011
DOI: 10.1111/j.1753-318x.2011.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Greenfield run off and flood estimation on small catchments

Abstract: Using evidence from 46 gauged small catchments in the United Kingdom, this paper demonstrates that the methods most commonly used for estimating design flows and greenfield run off rates on small catchments do not perform as well as alternative methods. Their results show larger error and a bias towards underestimation of the median annual flood. In contrast, newer methods from the Flood Estimation Handbook (FEH), when applied to small catchments, tend to have lower error and less bias. The paper investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…Geophysical factors that affect catchment runoff, such as soil condition, climate and land cover, can be easily configured by altering the input parameters in hydrological models [21,23]. Furthermore, hydrological models provide a reductionist way of characterizing various spatial scenarios in detail without considering the complexity of the real world [24,25,26]. As such, model-based analysis is necessary to generalize the specific hydrological process, and thus provides guidance for future urban storm water management efforts [27].…”
Section: Introductionmentioning
confidence: 99%
“…Geophysical factors that affect catchment runoff, such as soil condition, climate and land cover, can be easily configured by altering the input parameters in hydrological models [21,23]. Furthermore, hydrological models provide a reductionist way of characterizing various spatial scenarios in detail without considering the complexity of the real world [24,25,26]. As such, model-based analysis is necessary to generalize the specific hydrological process, and thus provides guidance for future urban storm water management efforts [27].…”
Section: Introductionmentioning
confidence: 99%
“…(), more recent studies by Faulkner et al . (2009, ) found that it gave poorer flood estimates than either the FEH QMED equation or the Revitalised Flood Hydrograph method (ReFH) discussed in the following sections. The Environment Agency (2009) also concluded that QMED estimates based on IH 124 are, on average, 39% too small.…”
Section: Current Methods Of Flood Estimationmentioning
confidence: 99%
“…Urbanised catchments (URBEXT1990 > 0.125) where floods occur predominantly in the summer half of the year, and highly permeable (BFIHOST >0.65) catchments, were also poorly represented in the datasets used to calibrate the ReFH model. Faulkner et al (2011), who used the evidence from 46 gauged catchments in the UK to investigate the theoretical and empirical support for various methods of design flood estimation found that: • Although the ReFH method had a fairly low bias when considering the entire dataset, this overall average masked the fact that the method tended to underestimate QMED for permeable catchments and overestimate QMED for less permeable and wet catchments (i.e. SAAR >800 mm); and • The combination of high permeability and part urbanisation appeared to result in particularly poor performance from ReFH.…”
Section: Revitalised Flood Hydrograph Methods (Refh)mentioning
confidence: 99%
See 2 more Smart Citations